Activities of Curcuma heyneana Rhizome and Graptophyllum pictum Leaves Combination against Staphylococcus aureus - Achmad Januar Er Putra; Sutji Kuswarini; Nurmawati Fatimah; Wening Hapsari (Asian Journal of Health Research, 2023)
Introduction: Infectious diseases have always been a problem, especially in the third-world countries. Due to the uncontrolled prescription of antibiotics, several bacteria developed resistance to some antimicrobial agents. One of them is Staphylococcus aureus. There is local wisdom in Indonesia to use natural products as potent antimicrobial agents. Curcuma heyneana and Graptophyllum pictum had been used by the locals in past centuries and seemed to be an effective agent for combatting infectious diseases. Therefore, we want to evaluate the activity of the combined extract of Curcuma heyneana and Graptophyllum pictum against Staphylococcus aureus.. Material and Methods: An in-vitro test by using the test tube dilution. The test tubes consisted of seven tubes; 2 control tubes and 5 experimental tubes. We used 1000mg/ml of each extract component at the highest (i.e., 1000mg/ml for Curcuma heyneana and Graptophyllum pictum, respectively). Five-times replication was conducted for each treatment. MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) were investigated after being streaked at the agar plate and incubated at 370C for 24 hours. Results: We could not determine the MIC because the colour of the combination of the extract was cloudy. The bacteria grew at all concentrations from five-times replication, except for the negative control, therefore MBC could not be obtained. Conclusion: Staphylococcus aureus was not inhibited effectively by combined extract of Curcuma heyneana and Graptophyllum pictum.